Natural Fractures in Low-Permeability Sandstone Reservoirs in the LD-A HPHT Gas Field, Yinggehai Basin: Implications for Hydrocarbon Exploration and Development - Li, Hui; Fan, Caiwei; Jiang, Zhenxue; Li, Jun; Li, Chao; Xu, Xuhui; Li, Fang; Hu, Gaowei (Frontiers in Earth Science, 2022)
Research on the characteristics and distribution of natural fractures is of great importance for the exploration and development of low-permeability sandstone gas reservoirs. In this study, fracture identification and characterization were carried out using cores and imaging logging. Then, comprehensive fracture development indicators were constructed to predict the distribution of fractures in wells by conventional logging. The main factors that affect the development of natural fractures and the implications of fractures on hydrocarbon exploration and development were discussed. The results showed that the natural fractures were mainly low-angle tectonic fractures in sandstone reservoirs. Most of fractures are unfilled, but the distribution of the fractures in the thin sections has a discrete fracture structure, indicating that the connectivity of the fracture system is poor. The development of natural fractures is mainly influenced by rock strength, petrographic composition, and petrology, and the fractures are more developed in sandstones with a higher content of brittle minerals. The fracture densities are mainly distributed below 0.05 m/m and up to 0.1 m/m. In the present in situ stress state, all of the natural fractures in the LD-A gas field are invalid fractures. The critical pressure of the natural fracture is approximately 16.5–25.4 MP/km; when the pore pressure exceeds this value, the fractures become effective fractures. These results provide new geological knowledge and guidance for the exploration and development of LD-A gas fields and other low-permeability tight sandstone reservoirs.